"Connect, " Log It, Track It, Go! Techne—Not Technology—and Embodiment to Achieve Phronesis in Exercise Promotion. Issue 1 (2nd January 2018) - Kosma, Maria; Buchanan, David R.
ABSTRACT: Given the rise in obesity and the positive exercise effects in curbing obesity levels, exercise promoters are expected to use technological applications—social media and fitness applications—in their exercise motivational programs. The purpose of this article is to critique the use of social media and fitness apps as both ineffective and potentially harmful. An alternative approach is proposed where phronesis (practical wisdom) in exercise participation can be achieved via physical and cognitive mastery of the action for its own sake ( real techne -art, embodiment). Emphasizing exercise outcomes (e.g., energy expenditure) captured by external devices distracts from embodied and phronetic action. Drawing on the philosophies of phronesis, techne, and embodiment, exercise promoters should emphasize embodied exercise experiences via mastery of action, social interactions, and connectedness to nature. They should target real action in real communities, and not emotionless and meaningless online forums about how to become the ultimate virtual fitness buff.